Writers of the Reign of Henry II
VIII, 280 p.
Keywords: This collection of work studies the often neglected writers of the second half of the twelfth century in England. At this time three languages competed for recognition and prestige and carved out their own spaces, while an English-speaking populace was ruled by a French-speaking aristocracy and administered by a Latin-speaking and writing clergy.